RESPONSE TO THE MINISTRY OF RELIGIOUS AFFAIRS' QUR ‘ANIC TRANSLATIONS: A Case Study of The Emergence of UII Qur'anic Translations - Rosyada, Melynia; Syihabuddin, Muhammad; Manggala, Kayan (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2024)
Studies in Qur'an translation projects today focus on translation projects by government institutions and individuals, even though non-government institutions also contribute to Qur'an translation projects in Indonesia. This article discusses the production of the translation of the Qur'an by the Islamic University of Indonesia (UII), namely